Estimation of Turkey Electric Energy Demand until Year 2035 Using TLBO Algorithm - TEFEK, Mehmet Fatih; UGUZ, Harun (Prof. Dr. Ismail SARITAS, 2016)
In this study, the estimation of Turkey primary electric energy demand until 2035 is tried to estimate by using Teaching-Learning Based Optimization (TLBO) Algorithm. Two models are proposed which are based on economic indicators TLBO algorithm linear energy demand (TLBOEDL) and TLBO algorithm quadratic energy demand (TLBOEDQ). In both of these two models the indicators used are Gross Domestic Product (GDP), population, importation and exportation. After a comparison of these two models with real values between 1979 and 2005 years, it is applied to the estimation of Turkey electric energy demand until 2035 by three different scenario. The estimation results are suitable with the estimation of Turkey total primary energy supply of 2013 Energy Report of World EnergyÃ‚Â Council Turkish National CommitteeÃ‚Â (WEC-TNC ).Ã‚Â Ã‚Â